Theoretical study of the atrazine pesticide interaction with pyrophyllite and Ca2+‐montmorillonite clay surfaces. Issue 3 (12th November 2016) - Belzunces, Bastien; Hoyau, Sophie; Benoit, Magali; Tarrat, Nathalie; Bessac, Fabienne
Abstract : Atrazine, a pesticide belonging to the s ‐triazine family, is one of the most employed pesticides. Due to its negative impact on the environment, it has been forbidden within the European Union since 2004 but remains abundant in soils. For these reasons, its behavior in soils and water at the atomic scale is of great interest. In this article, we have investigated, using DFT, the adsorption of atrazine onto two different clay surfaces: a pyrophyllite clay and an Mg‐substituted clay named montmorillonite, with Ca 2+ compensating cations on its surface. The calculations show that the atrazine molecule is physisorbed on the pyrophyllite surface, evidencing the necessity to use dispersion‐corrected computational methods. The adsorption energies of atrazine on montmorillonite are two to three times larger than on pyrophyllite, depending on the adsorption pattern. The computed adsorption energy is of about −30 kcal mol −1 for the two most stable montmorillonite‐atrazine studied isomers. For these complexes, the large adsorption energy is related to the strong interaction between the chlorine atom of the atrazine molecule and one of the Ca 2+ compensating cations of the clay surface. The structural modifications induced by the adsorption are localized: for the surface, close to substitutions and particularly below the Ca 2+ cations; in the molecule, around the chlorine atom when Ca 2+ interacts strongly with this basic site in a monodentate mode. This study shows the important role of the alkaline earth cations on the adsorption of atrazine on clays, suggesting that the atrazine pesticide retention will be significant in Ca 2+ ‐montmorillonite clays. © 2016 Wiley Periodicals, Inc. Abstract : The important role of the alkaline earth cations on the adsorption of atrazine on clays is shown, suggesting that the pesticide retention will be significant on Ca 2+ ‐montmorillonite surface.